Biología de Protospirura muricola Gedoelst, 1916 y Mastophorus muris (Gmelin, 1790) (Nematoda: Spiruridae), en Costa Rica. II. Huéspedes definitivos - Campos Q., Mariana; Vargas V., Mario (Revista de Biología Tropical, 1978)
A sample of 100 Rattus norvegicus were collected in the Central Market of San José, Costa Rica and when dissected two species of spirurids were found: Protospirura muricola (Gedoelst, 1916) (14%) and Mastophorus muris (Gmelin, 1790) (59%). Both genera and species were recognized by examination of the following structures: buccal capsule, spicules and position of the vulva. Their measurements are the only statistically valid guidelines since other structures show great interspecific and intraspecific variation. Mastophorus muris is reported for the first time in Costa Rica in Rattus norvegicus. The size of the eggs of both species, determined by the transversal and longitudinal diameters makes it possible to separate them at this stage of development. Inoculation of 14 white rats with spirurid capsules obtained from naturally infected Leucophaea maderae yielded in serial dissections 90 larvae and 40 adults, characteristic of P. muricola, confirming that this roach is a natural intermediate host of this nematode in Costa Rica. A comparative study of the measurement of different structures of 15 infective larvae of P. muricola, some mounted in polyvinyl alcohol and others measured in vivo, did not show significant variations. An experimental inoculation of a spider monkey (Ateles geoffroyi) with spirurid capsules obtained from naturally infected Leucophaea maderae yielded 26 adult nematodes that were identified as P. muricola. It is significant that the pathological changes caused by P. muricola are not apparent in Rattus norvegicus as they are in Ateles geoffroyi.